Flexural behavior of epoxy composites reinforced with banana fibers in different architectures: experimental, analytical, and numerical approaches - Shahapurkar K.; M. C K.; Chenrayan V.; Kanaginahal G.; Gebremaryam G.; Nik-Ghazali N.-N.; Kuan T.M.; Ariffin A.M.; Arunachalam A.; Fouad Y.; Soudagar M.E.M. (Springer Science and Business Media Deutschland GmbH, 2025)
In the present investigation, banana fibers extracted from Ethiopia are utilized to fabricate the composites with different fiber architectures in the epoxy matrix. Six different types of composites?untreated/treated chopped banana epoxy composite (UCBEC/TCBEC), untreated/treated woven banana epoxy composite (UWBEC/TWBEC), and untreated/treated chopped banana woven banana epoxy composite (UCBWBEC/TCBWBEC)?are prepared with the hand layup technique. The prepared composites are subjected to three-point flexural tests to confirm the structural integrity. Flexural strength and modulus of all the composites were evaluated experimentally while numerical simulation was performed using finite element analysis (FEA) to validate the results. Experimental results showed that TWBEC (treated woven banana epoxy composite) composites attained an 11 to 25% higher flexural strength than other compositions due to fiber treatment and weaving patterns. Additionally, the interaction between fiber and matrix was explored through appropriate theoretical modeling. Results inferred that full-oriented, continuous woven matting reinforcements increase shear strength while chopped fiber reinforcement has decreased shear strength due to discontinuity and higher aspect ratio. A scanning electron microscope was used to examine post-fracture surfaces to look into the failure process. The results of the numerical simulation are utilized in order to validate the findings of the study. The numerical results are in good agreement with experimental findings with a 5% accuracy loss. Finally, the outcomes of the present study are compared with those of previous research, presented in the format of a property map. ? The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024.